2019
DOI: 10.1038/s41598-019-39769-z
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Limk1 and Limk2 in mice does not alter cochlear development or auditory function

Abstract: Inherited hearing loss is associated with gene mutations that result in sensory hair cell (HC) malfunction. HC structure is defined by the cytoskeleton, which is mainly composed of actin filaments and actin-binding partners. LIM motif-containing protein kinases (LIMKs) are the primary regulators of actin dynamics and consist of two members: LIMK1 and LIMK2. Actin arrangement is directly involved in the regulation of cytoskeletal structure and the maturation of synapses in the central nervous system, and LIMKs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 65 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…Knockdown Arhgef6 in mice caused progressive hearing loss due to HC loss and stereocilia deficits ( Zhu et al, 2018 ). Fang et al (2019) reported that loss of Limk1 and Limk2 did not affect the overall development of the cochlea and the structure of hair bundles. CCDC154 is not necessary for the survival of hair cells or spiral ganglion cells.…”
Section: Discussionmentioning
confidence: 98%
“…Knockdown Arhgef6 in mice caused progressive hearing loss due to HC loss and stereocilia deficits ( Zhu et al, 2018 ). Fang et al (2019) reported that loss of Limk1 and Limk2 did not affect the overall development of the cochlea and the structure of hair bundles. CCDC154 is not necessary for the survival of hair cells or spiral ganglion cells.…”
Section: Discussionmentioning
confidence: 98%
“…HCs in the inner ear cochlea function in transducing sound waves into electric signals [17][18][19][20][21], while supporting cells function in supporting the HCs and providing the potential pool for HC regeneration [22][23][24][25][26]. Damages from a variety of sources can impair HC function, including genetic factors, aging, ototoxic drugs, chronic cochlear infections, and noise exposure [19,[27][28][29][30][31]. In this study, we reported the protective effect of Clusterin deficiency against age-related hearing loss and drug-induced ototoxicity, which are both due to irreversible loss of sensory HCs [32][33][34][35][36] and degeneration of the spiral ganglion neurons (SGNs) [37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Whole-mount immunohistochemistry was performed as previously described ( Fang et al, 2019 ). The cochleae were dissected from the temporal bones in cold PBS and were then fixed in 4% polyoxymethylene (Sigma,158127) for 1 h, followed by permeabilization with 0.1% Triton X-100 (Solarbio, T8200-500) for 1 h. After blocking (10% donkey serum, 0.5% Triton X-100, and 1% BSA in PBS at pH 7.2) for 1 h at room temperature, the sensory epithelia were incubated with the following primary antibodies overnight at 4°C: anti-Kir5.1 (Abnova, PBA-18407); anti-Myo7A (Proteus Bioscience, 25-6790; DSHB,138-1); anti-Sox2 (Santa Cruz Biotechnology, sc-17320); anti-CtBP2 (BD Biosciences, 612044); and anti-PSD95 (Millipore, MAB1596).…”
Section: Methodsmentioning
confidence: 99%